The Importance of Using Bra Breast Care (BBC) to Overcome Nipple Problems in Postpartum Mothers in Praktik Mandiri Bidan (PMB) - Elly Wahyuni; Lusi Andriani; Epti Yorita; Sri Yanniarti (CV Media Inti Teknologi, 2022)
Mother's Milk is the best food for newborns and is the only healthy food that babies need in the first months of life. Breastfeeding has many benefits for both mother and baby. One of the obstacles to breastfeeding is problems with the mother's breasts because it gives difficulties for the baby to breastfeed, including flat, sunken and blistered nipples.Research conducted by Jannah, et al (2018) thatthe duration of successful breastfeeding in the intervention group given the BBC was a minimum of 3 and a maximum of 6 days, while in the control group given a nipple puller it was longer, namely a minimum of 6 days and a maximum of 22 days. The statistical test results showed that there was a significant difference in the mean duration of successful breastfeeding in mothers with inverted nipples given the BBC modification with a p=0.00, the mean difference being 9.4. This means that the use of the BBC modification can accelerate the success of breastfeeding in mothers with inverted nipples 9.4 times compared to mothers with nipple puller intervention. This community service activity method uses an approach to increasing knowledge, skills through webinar zoom meetings and training. The results of filling out the pre and post test questionnaires showed that the average pretest value was 66, 76 to 85.44 with an increase in knowledge of 21.86%. In conclusion, there is an increase in the knowledge and skills of alumni to produce BBC which can be seen in the video on the process of making the BBC and there is an additional type of service at PMB, namely BBC marketing. It is recommended that PMB and alumni open businesses and have an entrepreneurial spirit so that they can create job opportunities for other alumni and provide services to breastfeeding mothers who have problems with flat, sunken and chafed nipples.